E-learning in Economics and Business - Batalla, Josep M.; Rimbau, Eva; Serradell, Enric (International Journal of Educational Technology in Higher Education, 2014)
E-learning is broadening education horizons all over the world. The contribution sought by this work is to evidence innovations and practices that are applied to teaching environments and fields of knowledge connected with Economics and Business in an online environment. In this respect, some contributions relating to concepts and subjects considered as emergent are presented here. These are, for example, the acquisition of competencies in online environments, the use of Wikipedia applied to statistics, the use of tools offered by social networks or the subject of cooperative learning and teamwork. In addition to such contributions, we present some reflections on the most significant future trends of e-learning. In the near future, lecturers will be able to make decisions based upon a huge amount of information that it will be possible to generate after analysing the learning processes. All in all, everything seems to point towards four aspects that will be progressively incorporated into online learning: the release and democratisation of content, the addition of elements to motivate students, the efficient management of teaching and, lastly, the establishment of a tighter link between learning and profession.